A guide to facilitate the creation of a femoral tunnel for arthroscopic ligamentum teres reconstruction: A three-dimensional computed tomography study - İSMAİLOĞLU, ABDUL VELİ (My University, 2023)
Te ideal femoral tunnel passing through the centre of the femoral neck targeted to the footprint of the ligamentum teres (LT) is established during the LT reconstruction surgery with the free-hand technique. We aimed to quantitatively determine the entry site and defne the angular orientation of the ideal femoral tunnel with its relevance to the femoral valgus angle (FVA) and the femoral anteversion angle (FAA) to facilitate the creation of an ideal femoral tunnel during the LT reconstruction surgery. A total of 60 randomly selected CT images were obtained to reconstruct three-dimensional femur models. A virtual reamer representing the ideal femoral tunnel was placed in the femur models. Te femur length, FVA, FAA, the femoral tunnel anterior angle, the femoral tunnel superior angle and the skin- and bony-entry sites were measured. Te femoral tunnel angular orientation was strongly correlated with the FVA and the FAA. Mathematical formulas were defned by which entry site of the reamer and the anterior and superior angulation of the femoral tunnel could be estimated before the surgery. Te mean skin-entry site was 67.3 mm distal and 0.1 mm anterior to the centre of the greater trochanter’s superior border. Te angular orientation of the femoral tunnel using FVA and FAA can be easily estimated using mathematical formulas before LT reconstruction surgery. Te entry site and angular orientation of the femoral tunnel described in this study can be used to reduce dependency on the usage of fuoroscopy and the workload on the surgeon during the LT reconstruction surgery.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Anatomi; Medicine; Health Sciences; Fundamental Medical Sciences; Human Anatomy; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Biyoloji ve Biyokimya; TIP, GENEL & DAHİLİ; ANATOMİ VE MORFOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; BIOLOGY & BIOCHEMISTRY; MEDICINE, GENERAL & INTERNAL; ANATOMY & MORPHOLOGY; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Anatomy; Medicine (miscellaneous); General Medicine